(untitled) (Malaysian Journal of Civil Engineering, 2018)
Papua Province is one of the target areas of national development program in Indonesia. The development program covers the acceleration of road construction. The issue regarding this acceleration is the frequent occurrence of delay in the road construction project in Papua. This research delivers the risk rating of delay risk factors of road construction project in Papua. The delay risk factors are grouped into project factors; owner; contractor; consultant; design; materials; equipment; labor; external factor; finance and economic; and finance and political factors. Nine risks with high categories are generated from the risk assessment, which are (1) Social and Cultural Effect; (2) Physical factors in the working field; (3) Traffic obstruction within and around the project area; (4) Public security; (5) Ineffective delay penalties; (6) A poor relationship with local communities; (7) Lack of productivity; (8) Change-order by owner during construction; and (9) Delay in revising designs by owner. The risks with high category should be mitigated by performing several methods since the early stage of the project. The methods include conducting public discussion, performing comprehensive field survey, performing adequate cost estimation, preparing a sufficient contract, and executing a proper site supervision system.